Osmotic pressure-dependent release profiles of payloads from nanocontainers by co-encapsulation of simple salts. Issue 26 (15th June 2016) - Behzadi, Shahed; Rosenauer, Christine; Kappl, Michael; Mohr, Kristin; Landfester, Katharina; Crespy, Daniel
Abstract : Osmotic pressure-dependent release of payloads from nanocapsules can be applied for controlled release of self-healing agents or drugs. Abstract : The encapsulation of payloads in micro- to nano-scale capsules allows protection of the payload from the surrounding environment and control of its release profile. Herein, we program the release of hydrophilic payloads from nanocontainers by co-encapsulating simple inorganic salts for adjusting the osmotic pressure. The latter either leads to a burst release at high concentrations of co-encapsulated salts or a sustained release at lower concentrations. Osmotic pressure causes swelling of the nanocapsule's shell and therefore sustained release profiles can be adjusted by crosslinking it. The approach presented allows for programing the release of payloads by co-encapsulating inexpensive salts inside nanocontainers without the help of stimuli-responsive materials.